Encyclopedia of lifestyle medicine & health - Rippe, James M. (Sage Publications, 2012)
"The Encyclopedia of Lifestyle Medicine and Health offers thorough coverage of relevant topics and issues in historical and contemporary context, with information on lifestyle habits and practices and their impact on health. These three volumes sort out the science behind nightly news reports and magazine cover stories, helping the reader to discern sound, evidence-based advice from that which is merely fad. The volumes convey the latest research on lifestyle medicine, incorporating content from such areas as health psychology, communication, public policy and health promotion, and disease prevention, among others. Researchers are empowered to lead and promote healthier lifestyles after perusing the hundreds of signed, authoritative entries written by leading experts in their respective fields. Accompanying bibliographies and suggested readings provide guidance toward more in-depth resources. This comprehensive reference resource is written accessibly, making it useful for a broad audience, including students and academics in the fields of health, physical education, biology, medicine, nursing and allied health, physical therapy, nutrition, public health, and health communication, as well as for lay readers interested in learning how to leader a healthier lifestyle"--Provided by publisher.